Simvastatin Inhibits Endotoxin-Induced Apoptosis in Liver and Spleen Through Up-Regulation of Survivin/NF-κB/p65 Expression - Nežić, Lana; Amidžić, Ljiljana; Škrbić, Ranko; Gajanin, Radoslav; Nepovimova, Eugenie; Vališ, Martin; Kuča, Kamil; Jaćević, Vesna (Frontiers in Pharmacology, 2019)
Endotoxemia is associated by dysregulated apoptosis of immune and non-immune cells. We investigated whether simvastatin has anti-apoptotic effects, and induces hepatocytes and lymphocytes survival signalling in endotoxin-induced liver and spleen injuries. Wistar rats were divided into the groups pretreated with simvastatin (20 or 40 mg/kg, orally) prior to a non-lethal dose of LPS, the LPS group, and the control. The severity of tissue inflammatory injuries was expressed as hepatic (HDS) and spleen damage scores (SDS), respectively. The apoptotic cell was detected by TUNEL (Terminal deoxynucleotidyl transferase dUTP Nick End Labeling) and immunohistochemical staining (expression of cleaved caspase-3, and anti-apoptotic Bcl-xL, survivin and NF-κB/p65). Simvastatin dose-dependently abolished HDS and SDS induced by LPS (p < 0.01), respectively. Simvastatin 40 mg/kg significantly decreased apoptotic index and caspase-3 cleavage in hepatocytes and lymphocytes (p < 0.01 vs. LPS group, respectively), while Bcl-XL markedly increased accordingly with simvastatin doses. In the simvastatin, groups were determined markedly increased cytoplasmic expression of survivin associated with nuclear positivity of NF-κB, in both hepatocytes and lymphocytes (p < 0.01 vs. LPS group). Cell-protective effects of simvastatin against LPS seemed to be mediated by up-regulation of survivin, which leads to reduced caspase-3 activation and inhibition of hepatocytes and lymphocytes apoptosis.